Pengaruh Citra Merek, Kualitas Produk, Harga, dan Gaya Hidup Hedonisme terhadap Keputusan Pembelian - Diandini, Dyndha; Wiyadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Developments in the smartphone industry are currently very fast and varied. A smartphone product is required to have a good perspective for consumers because it is not uncommon for the depiction of a particular brand to be related to a person's lifestyle, therefore companies must always innovate, maintain quality, and create good smartphone products so that the products offered sell well on the market and are in demand among people. lots of consumers. The target of this study is to examine the influence of brand image, product quality, price and hedonistic lifestyle on purchasing decisions. Data was collected from 162 respondents in the SoloRaya area who met certain criteria. The sampling technique used in this research is the purposive sampling method, then the data is processed using Multiple Linear Regression analysis tools with SPSS analysis software version 22. The results of the study show that 1) Brand image has a positive and significant influence on purchasing decisions. 2) Product quality has a positive and significant influence on purchasing decisions. 3) Price has a positive and significant influence on purchasing decisions. 4) The hedonistic lifestyle has a significant positive influence on purchasing decisions. Suggestions for company managers to always maintain high product quality and always innovate in design and features as well as launch effective marketing and pay attention to consumer needs and desires. So this has an impact on creating higher purchasing decisions for iPhone smartphones. Researchers who are interested in carrying out similar research titles are expected to add other variables, for example: Brand love, Brand equity, social factors, and Promotion.